Representasi Selflessness Perempuan Indonesia dalam Film Home Sweet Loan - Rambu Naha (Jurnal Nomosleca, 2025)
This study examines the representation of Indonesian women in the film Home Sweet Loan (2024) using Roland Barthes’ semiotics to analyze meaning production at the levels of denotation, connotation, and myth. The findings reveal that the film constructs female selflessness through three narrative themes: (1) the responsibilities of daughters within the family, (2) the negotiation between modern womanhood and selflessness, and (3) the positive incentives given to women who sacrifice their personal aspirations. Although the character Kaluna is portrayed as an urban woman with the agency to express discomfort and negotiate her boundaries, the narrative ultimately directs her toward prioritizing family needs, reaffirming the myth of the ideal Indonesian woman within a patriarchal cultural framework. At the same time, the presence of a female director introduces an emotional framing that opens a reflective space regarding gendered burdens experienced by women. This study is limited to a single film and descriptive semiotic analysis without incorporating audience perspectives. Future research should explore audience reception or conduct comparative studies across multiple films to deepen the understanding of gender ideology in Indonesian cinema.